A role of vertical mixing on nutrient supply into the subsurface chlorophyll maximum in the shelf region of the East China Sea. (1st July 2017) - Lee, Keunjong; Matsuno, Takeshi; Endoh, Takahiro; Ishizaka, Joji; Zhu, Yuanli; Takeda, Shigenobu; Sukigara, Chiho
Abstract: In summer, Changjiang Diluted Water (CDW) expands over the shelf region of the northern East China Sea. Dilution of the low salinity water could be caused by vertical mixing through the halocline. Vertical mixing through the pycnocline can transport not only saline water, but also high nutrient water from deeper layers to the surface euphotic zone. It is therefore very important to quantitatively evaluate the vertical mixing to understand the process of primary production in the CDW region. We conducted extensive measurements in the region during the period 2009–2011. Detailed investigations of the relative relationship between the subsurface chlorophyll maximum (SCM) and the nitracline suggested that there were two patterns relating to the N/P ratio. Comparing the depths of the nitracline and SCM, it was found that the SCM was usually located from 20 to 40 m and just above the nitracline, where the N/P ratio within the nitracline was below 15, whereas it was located from 10 to 30 m and within the nitracline, where the N/P ratio was above 20. The large value of the N/P ratio in the latter case suggests the influence of CDW. Turbulence measurements showed that the vertical flux of nutrients with vertical mixing was large (small) where the N/P ratio was small (large). A comparison with a time series of primary production revealed a consistency with the pattern of snapshot measurements, suggesting that the nutrient supply from the lower layer contributes considerably to the maintenance of SCM. Highlights: Turbulent nutrient supply was compared with primary production around the SCM. Vertical mixing plays an important role on the primary production in the ECS. Difference of the nutrient fluxes associated with N/P ratio is statistically significant.